2018
DOI: 10.34239/ajops.v1i2.46
|View full text |Cite
|
Sign up to set email alerts
|

Part of the problem or part of the solution? Plastic surgeons and body image dissatisfaction

Abstract: The prevalence of body dissatisfaction amongst people of all ages is increasing year on year. A substantial body of evidence now attests to a range of negative impacts on psychological wellbeing and on key areas of living, including health, education, work and relationships. This article considers why this social issue is worthy of attention from plastic surgeons and their teams and outlines ways in which the profession might contribute to a collective response. Suggestions include education to enhance underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that healthcare professionals sometimes fail to address their patients' worries and emotions [90] , which can lead to longer consultation times [89] . Conversely, directly addressing patients' concerns and worries often leads to shorter consultation times [91] .…”
Section: Module Three: Improving Patient Care: Communicationmentioning
confidence: 99%
“…Research has shown that healthcare professionals sometimes fail to address their patients' worries and emotions [90] , which can lead to longer consultation times [89] . Conversely, directly addressing patients' concerns and worries often leads to shorter consultation times [91] .…”
Section: Module Three: Improving Patient Care: Communicationmentioning
confidence: 99%